A sensitivity analysis of dual-polarization features to damage due to the 2016 Central-Italy earthquake. Issue 20 (18th October 2018) - Ferrentino, E.; Nunziata, F.; Migliaccio, M.; Vicari, A.
ABSTRACT: In this study, the sensitivity of dual-polarization features extracted from dual-polarimetric coherent synthetic aperture radar (SAR) imagery to urban damage due to the earthquake occurred in Central -Italy in 2016 is addressed. First, a conventional single-polarization feature, based on the coherence between pre- and post-event co-polarized imagery, is analysed using SAR scenes collected by the Copernicus Sentinel-1 mission over the area of Amatrice, an Italian city significantly damaged by the 2016 earthquake that affected Central Italy. Then, the same analysis is undertaken using the cross-polarized channel to point out that the joint use of co- and cross-polarized channels can help in better observing the damaged area. Finally, a coherent dual-polarimetric feature, based on the inter-channel coherence, is proposed. This feature results in a sensitivity to damaged areas comparable to the one provided by conventional single-polarization features. However, the interchannel coherence has the benefit to be based only on two SAR acquisitions, i.e. before and after the earthquake and it is less affected by false alarms. SAR, polarimetry, earthquake, losses